Стратегические ориентиры компании-товаропроизводителя в современных условиях хозяйствования - Fateeva S. V., Barkar N. I. (Economics and management: problems, trends and future development, 2017)
The article is devoted to using the tools of strategic analysis in defining the strategic orientation of the company. The object of the study were a large company with the brand of "Shakhtinskaya plitka", which at the moment is trying to change their market rate.
Keywords: SWOT-анализ; предприятие; стратегия; стратегический анализ; strategy; SWOT analysis; Shakhtinskaya plitka; tools for strategic analysis